Application vs. non-application contexts in Euclidean geometry tasks in grades 10–12 South African mathematics textbooks - Zhou, Tinevimbo; Ogbonnaya, Ugorji l. (Universitas Islam Negeri Raden Intan Lampung, 2026)
Mathematical knowledge and ideas are shaped by cultural context, and context can influence mathematics teaching and learning. Contextualising mathematical problems provides relevance, meaning, and application to mathematical concepts, making them more accessible and engaging for students. This study investigated the contextual features of Euclidean geometry tasks in nine Grade 10-12 South African mathematics textbooks. The study employed a deductive content analysis approach to analyse Euclidean geometry tasks in the textbooks. The study focused on determining whether the tasks presented in the textbooks incorporated application (real-world) or non-application (abstract/intra-mathematical) contexts, based on a framework adapted from Zhu and Fan. A total of 2338 tasks were analysed across the textbooks. Findings revealed an overwhelming dominance of non-application tasks, with no geometry tasks presented in a real-life context. The lack of real-life contextual tasks in the textbooks may limit students' opportunities to connect mathematical concepts with everyday experiences, thereby restricting their development of problem-solving, critical thinking, and engagement, ultimately impacting students’ achievement and perception of the relevance of Euclidean geometry. We recommend incorporating more authentic, context-rich tasks into Euclidean geometry tasks in textbooks to enhance students’ opportunities to learn and their ability to apply Euclidean geometry concepts in meaningful ways. This highlights the need for collaborative curriculum and textbook design that presents mathematics as meaningful and culturally grounded.